Agriculture Trade and Price Policy in Pakistan - Valdés, Alberto (World Bank, Washington, DC, 2014)
This policy paper focuses on the incentive framework for Pakistani agriculture, with emphasis on trade and price policies. It first presents a synthesis of major trends in the performance of the sector and analyzes Pakistan's extraordinarily complex, opaque and discretionary, and continually-changing trade regime. It presents a disaggregated analysis of the border measures for the selected products (trade and price interventions vary by product), and estimates the joint effect of trade and procurement policies on farm prices, captured by direct price comparison. It concludes by providing policy recommendations emphasizing on the revision of trade regime to eliminate quantitative restrictions and to modify tariffs in the direction of greater equality, a positive, moderate and uniform tariff on imports across the board as the only border measure for import competing products.